Hubungan Healthy Eating Index Dengan Kenaikan Berat Badan Ibu Selama Kehamilan Di Sumatera Barat - Riska Helfina (Majalah Kedokteran Andalas, 2023)
AbstractObjective: To determine the association between the healthy eating index of pregnant women and maternal weight gain during pregnancy in West Sumatra.Methods: Research with a cross-sectional design in West Sumatra on 110 pregnant women.This research is an analysis of secondary data from the study "Giving Dadiah on pregnancy and birth outcomes in West Sumatra".The study used data from 24-hour recall of pregnant women in the first trimester, second trimester and third trimester and pregnant women's weight data.Results: The study showed that there was a relationship between the HEI of pregnant women and the increase in maternal weight during pregnancy with p = 0.049 with a value of r = 0.188.Conclusion: There is a relationship between the healthy eating index of pregnant women and the increase in maternal weight during pregnancy.Keywords:  healthy eating index; weight gain; pregnant woman